AB0462 Up to 5-year retention of abatacept in belgian patients with moderate-to-severe ra: prospective data from the real-world action study. (12th June 2018) - Westhovens, R.; Connolly, S.E.; Margaux, J.; Vanden Berghe, M.; Maertens, M.; Van Den Berghe, M.; Elbez, Y.; Chartier, M.; Baeke, F.; Robert, S.; Malaise, M.
Abstract : Background: With its specific mechanism of action, abatacept (ABA) has shown good efficacy, acceptable safety and is well tolerated in patients (pts) with RA in randomised clinical studies. 1, 2 In a chronic disease such as RA, the long-term efficacy and safety of treatment are crucial and require validation in a real-world setting. Objectives: To explore long-term safety and retention in pts with RA treated with IV ABA in routine clinical practice in the Belgian cohort of the AbataCepT In rOutiNe clinical practice (ACTION) study. Methods: ACTION is a noninterventional, multicentre, prospective, longitudinal study of pts (aged >18 years) with established active moderate-to-severe RA, who initiated IV ABA in routine care. 3 In Belgium, reimbursement criteria require failure with 2 conventional synthetic DMARDs and DAS28 (CRP) >3.7. The primary study objective was retention rate estimated using the Kaplan–Meier method. Results: Overall, 135 Belgian pts from 16 sites (6 [4.4%] first-line biological and 129 [95.6%] second or further line) were enrolled between October 2010 and December 2012. Of these, 131 were evaluable for effectiveness analysis. Pts had a mean (SD) disease duration of 10.5 (9.7) yrs and were at high risk of disease progression: 25.4% of the evaluable pts had erosions (n/n=33/130), 71.6% were anti-cyclic citrullinated peptide positive (n/n=63/88) and 76.7% were RF positive (n/n=79/103). Overall, pts showed high disease activity at baseline according to mean (SD) DAS28 (ESR) 5.21 (1.02), DAS28 (CRP) 4.72 (1.09), CDAI 28.5 (11.1), SDAI 29.9 (11.9) and HAQ-DI score 1.23 (0.65). Patient and Physician Global Assessment of disease were mean (SD) 65.3 (20.95) and 58.02 (21.77), respectively. The overall retention rate (95% CI) was 76% (68.8, 82.5), 64% (54.8, 71.5) and 34% (22.6, 45.4) at 12, 24 and 60 mths, respectively. When temporary discontinuations (>84 days, n=24) were not included in the number of events, retention rates were 80% (72.0, 85.9), 73% (64.0, 79.4) and 51% (40.1, 61.0) at 12, 24 and 60 mths, respectively (Fig). Average DAS28 (CRP) before discontinuation and at restart was stable (3.37 [1.30] vs 3.73 [1.78], respectively [n=12]), suggesting that a temporary discontinuation of >2 consecutive ABA infusions does not seem to have a major clinical consequence. Pts who discontinued ABA due to lack of efficacy (n=37) had significantly shorter disease duration, higher CRP, higher number of prior DMARDs at baseline, mean DAS28 (CRP) of 3.61 (1.17) and DAS28 (ESR) of 4.66 (1.35) at discontinuation. Overall, ABA was generally well tolerated and no new safety signals were identified. Conclusions: These real-world data demonstrate an acceptable safety profile for abatacept in Belgian pts with a stable retention rate of up to 5 years in a difficult-to-treat population. A temporary discontinuation also seems feasible. References: [1] Westhovens R, et al. Clin Exp Rheumatol2014;32:553–62. [2] Genovese MC, et al. J Rheumatol2012;39:1546–54. [3] Nüßlein HG, et al. Clin Exp Rheumatol2016;34:489–99. Disclosure of Interest: R. Westhovens Grant/research support from: Bristol-Myers Squibb, Roche, Janssen, Consultant for: Celltrion, Galapagos-Gilead, S. Connolly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, J. Margaux: None declared, M. Vanden Berghe: None declared, M. Maertens Grant/research support from: Roche, Pfizer, M. Van Den Berghe: None declared, Y. Elbez: None declared, M. Chartier Employee of: Bristol-Myers Squibb, F. Baeke Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Robert Employee of: Bristol-Myers Squibb, M. Malaise: None declared